1993
DOI: 10.1677/jme.0.0110283
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Pit-1 and related proteins in diverse human pituitary adenomas

Abstract: Pit-1, a member of the POU family of homeo-domain transcription factors, activates prolactin and GH gene expression but also has a role in pituitary cell differentiation and proliferation. Expression of Pit-1 may therefore be of central importance in the function and phenotype of human pituitary adenomas. We have found evidence that, in addition to Pit-1 mRNA, Pit-1-like immunoreactivity and DNA-binding activity are readily detectable in a series of human pituitary adenomas. Gel mobility shift assays using ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
2
11
0
1
Order By: Relevance
“…3 Reliability from daughter information (values shown are for h 2 = 0.25). 4 Weight computed as 4 × reliability/(4 -1.5 × reliability) (values shown are for h 2 = 0.25). 5 Deregressed proofs for final score reported on the original scale, and linear scores reported on a relative scale.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…3 Reliability from daughter information (values shown are for h 2 = 0.25). 4 Weight computed as 4 × reliability/(4 -1.5 × reliability) (values shown are for h 2 = 0.25). 5 Deregressed proofs for final score reported on the original scale, and linear scores reported on a relative scale.…”
Section: Datamentioning
confidence: 99%
“…The growth hormone factor-1/pituitary-specific transcription factor, Pit-1, a member of the POU family of homeo-domain transcription factors, activates gene expression for thyrotropin and prolactin ( PRL) and growth hormone ( GH) but also has a role in pituitary cell differentiation and proliferation (4,15). The inhibition of Pit-1 synthesis leads to a marked decrease in expression of PRL and GH and to a dramatic decrease in proliferation of cell lines producing PRL and GH ( 8 ) .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the pituitary-specific transcription factor Pit-1, a member of a family of the POU-domain DNA-binding factors, has been shown to regulate growth hormone (GH), prolactin (PRL), and thyroid-stimulating hormone (TSH) cells during development and differentiation (5)(6)(7)(8)(9)(10)(11)(12). Neuro D1, a basic helix-loop-helix transcription factor, is expressed in corticotroph cells and contributes to the corticotroph-specific POMC transcription in the pituitary (13,14).…”
mentioning
confidence: 99%
“…In two ICC studies, Pit-1 was also unexpectedly observed in a limited number of ACTH-producing adenomas and clinically nonfunc tioning adenomas, although localization was found only in occasional cells [22,23]. Similarly, Hoggard et al [24] evidenced by Western blot and gel shift assay Pit-1-like immunoreactivity and DNA-binding activity not only in lactotropes and somatotropcs, but also in some nonfunc tioning adenomas. Altogether these data suggest that tumors classified as gonadotropes or null may be a more heterogeneous group, with a variety of lineages, than was previously suspected.…”
mentioning
confidence: 92%
“…A number of other reports [16][17][18][19][20][21][22][23][24] have examined human pituitary adenomas for Pit-1 gene expression. These studies, while not in total agreement, give insight into the origin of various pituitary tumors.…”
mentioning
confidence: 99%